2020
DOI: 10.1016/j.seizure.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic findings in COVID-19 patients: A systematic review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 51 publications
4
46
3
Order By: Relevance
“…We report on a cohort of 78 patients with COVID-19 who underwent EEG for a wide range of CNS manifestations. Recent case reports, small series, and meta-analyses assessing the value of EEG for patients with COVID-19 5 , 6 , 7 , 8 , 9 , 14 , 15 , 16 , 17 showed (1) nonspecific patterns, reflecting the diversity of SARS-CoV-2 infection complications, 1 , 7 , 9 , 14 , 15 , 16 , 17 or (2) a striking periodic EEG pattern, 5 , 6 , 8 , 17 suggestive of COVID-19–specific brain complications. Nevertheless, a systematic correlation of EEG findings with biological findings and brain MRI findings was lacking, precluding a better understanding of pattern origins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report on a cohort of 78 patients with COVID-19 who underwent EEG for a wide range of CNS manifestations. Recent case reports, small series, and meta-analyses assessing the value of EEG for patients with COVID-19 5 , 6 , 7 , 8 , 9 , 14 , 15 , 16 , 17 showed (1) nonspecific patterns, reflecting the diversity of SARS-CoV-2 infection complications, 1 , 7 , 9 , 14 , 15 , 16 , 17 or (2) a striking periodic EEG pattern, 5 , 6 , 8 , 17 suggestive of COVID-19–specific brain complications. Nevertheless, a systematic correlation of EEG findings with biological findings and brain MRI findings was lacking, precluding a better understanding of pattern origins.…”
Section: Discussionmentioning
confidence: 99%
“… 6 To our knowledge, few studies have evaluated EEG findings together with clinical, biological, and MRI findings in patients with COVID-19, and these studies did not show evidence of specific patterns. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Two systematic review studies with similar clinical questions have been previously reported [32] , [33] . Our meta-analysis provided additional value to those studies.…”
Section: Discussionmentioning
confidence: 84%
“…A prior systematic review of 177 patients reported that EEG findings are non-specific in COVID-19, with a majority (63.8%) of the cases having generalized slowing, 3.5% with normal EEG, and 19.2% with epileptiform activity [3] . Status epilepticus was reported in 4.5% of the patients [3] , comparable to 5% of patients in our study (4% nonconvulsive, 1% convulsive). Compared to a cohort study from New York City, our cohort exhibited similar rates of clinical seizures at 10% (12/110) of the patients which is comparable to that study of clinical seizures in 7% of the patients [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Seizures and status epilepticus (SE) have been reported with COVID-19, with new onset or exacerbation of existing epilepsy and the prevalence of seizures in patients with COVID-19 is still unknown. Multiple studies have recognized electroencephalography (EEG) changes in COVID-19, utilizing short- and long-term EEG recording, though no clear EEG pattern is reliably seen in this patient population [3] . Furthermore, the effects of seizures, clinical or subclinical (electrographic), on the functional outcome in critically ill patients with COVID-19 remains unclear.…”
Section: Introductionmentioning
confidence: 99%